COVID-19 vaccination status and associated factors among lactating women during the COVID-19 outbreak: a cross-sectional study in southern China. Issue 10 (21st October 2022) - Wang, Xiaofen; Tang, Kun; Huang, Rong; Yi, Simin
Abstract : Objectives: Different countries and institutions around the world have debated whether lactating women should receive the COVID-19 vaccine during the COVID-19 pandemic. In China, lactating is not a contraindication to vaccination, but many women are still hesitant to get vaccinated. The purpose of this study was to investigate the current status of COVID-19 vaccination among lactating women and the related factors affecting vaccination. Methods: An online cross-sectional survey involving 506 lactating women was conducted in southern China. We explored the related factors affecting COVID-19 vaccination of lactating women from three aspects: general information, knowledge–attitude–behaviour towards COVID-19 and its vaccine, and postpartum psychological state. Results: A total of 432 lactating women completed the questionnaire, 198 of whom had received the COVID-19 vaccine. On the knowledge–attitude–behaviour questionnaire on COVID-19 and its vaccines, the vaccinated group scored higher than the unvaccinated group on both the three subdimensions of the questionnaire and the total score (p<0.01). The results of binary logistics regression analysis showed that mixed feeding (OR=2.68, 95% CI: 1.82 to 3.96), longer breastfeeding duration (OR=1.31, 95% CI: 1.16 to 1.49), better physical condition (OR=5.28, 95% CI: 1.82 to 15.32), higher attitude score of COVID-19 and its vaccine (OR=1.18, 95% CI: 1.10 to 1.27), and having a travel history in medium high-risk areas (OR=3.49, 95% CI: 1.46 to 8.37) were significantly associated with COVID-19 vaccination in lactating women. Having a master's degree or above (OR=0.03, 95% CI: 0.01 to 0.30), and having higher anxiety score (OR=0.66, 95% CI: 0.54 to 0.81) and depression score (OR=0.84, 95% CI: 0.75 to 0.93) were inversely associated with COVID-19 vaccination in lactating women. Conclusion: 45.8% of lactating women were vaccinated against COVID-19. Education level, feeding methods, duration of breast feeding, travel history in medium high-risk areas, physical condition, attitude score of COVID-19 and its vaccine, anxiety symptom and depressive symptom score were associated with vaccination of lactating women. More interventions based on these factors were needed to reduce concerns for lactating women and increase their vaccination rates.